Social-envenomation : a ritual of snake-handling churches. - Waters, Amy (My University, 2018)
This study focused on the deaths that had taken place within the Pentecostal church sects that handled venomous snakes during their religious services. This was accomplished by gathering statistics of 105 cases that were found in literature. The data was gathered through an extensive literature review from online articles, books, and journals. The incidents that were studied occurred between the years 1900 through the most recent case in 2015. The various factors that were examined included: manner of death, gender of victims, age of the victims, date of the death, location of the death, relationship between victim and participating parties, and type of snake that envenomed the victims. Of the 105 cases that were gathered, the most prominent manner of death was deemed an accident. Males accounted for 74 percent of the deaths. The relationship between the victim and the party involved was a staggering 93 percent to a pastor and member. The date of a significant rise in deaths began in 1931 and remained steady until 1980. The ages of the victim were must numerable between the ages of 41-50 years of age, accounting for 25 percent. An overwhelming 33 percent of the deaths took place in Kentucky, with 63 percent of those deaths being accredited to the envenomation by rattlesnake.
Keywords: Snake cults (Holiness churches); Pentecostals; Poisonous snakes; Manner of death; Pentecostal; Rattlesnake; Snakebite; Snake-handlers; Social-envenomation